'Just ask "what if?" and go from there': the role of mainstream story structures in women's web series script development. Issue 1 (4th May 2021) - Taylor, Stayci
ABSTRACT: This article investigates, through interviews, the script development processes of four female-identifying web series creators, contributing to scholarship around web series' ability to serve diverse communities [Christian 2020. "Beyond Branding: The Value of Intersectionality on Streaming TV Channels." Television & New Media 21 (5): 457–474; 2011. "Fandom as Industrial Response: Producing Identity in an Independent Web Series." TWC – Transformative Works and Cultures, 8, 'Race and Ethnicity in Fandom' special issue; Monaghan 2017 . "Starting From … Now and the Web Series to Television Crossover: An Online Revolution?" Media International Australia 164 (1): 82–91; Williams 2012 . Web TV Series: How to Make and Market Them . Harpenden: Kamera Books], but from the perspective of the writing process. The three web series making up this small sample – Last Breath (2018), Love Songs (2019) and Phi and Me (2019-) – have all experienced notable levels of 'success' (defined here variously in terms of views, festival selections, and awards). This article offers a preliminary investigation into how women's web series writing practices may – or may not – depart from conventions that are practiced in mainstream settings of episodic script development, and/or are circulated by the screenwriting 'how-to' market. Using the insights into these writing processes, this article builds upon web series scholarship (where, it has been argued, innovations around diversity are leading the way in terms of screen content and distribution) by exploring the extent to which gender and cultural diversity, platform and standardised story structures inform the script development processes.